Up-regulation of miR-155 contributes to TNF-mediated hepatocyte apoptosis in acute liver failure - Guoqiang Zhang,; Chunyu Yan,; Dayang Chen,; Xiongbo Wu,; Yunan Zhang,; Qiang Zhan,; Fangmei An, (Turkish Journal of Gastroenterology, 2019)
Background/Aims: Acute liver failure (ALF) is due to severe immune response, resulting in massive apoptosis/necrosis of hepatocytes. The precise mechanism has not been explored yet. Materials and Methods: The mouse with ALF model was induced by D-GalN/LPS; the hepatic miRNAs expression profile was evaluated by miRNA microarray and verified by RT-PCR. During the ALF in mice, the miR-155 expression was detected in the liver as well as in spleen. Then the correlation between miR-155 and inflammatory cytokines was evaluated. Furthermore, the miR-155 expression in activated Raw264.7 cells and apoptotic hepatocytes was also studied. Finally, the regulatory roles of miR-155 in TNF expression of apoptotic hepatocytes were shown. Results: It was shown that miRNAs changed in the mice with ALF relating to hepatocytes apoptosis/necrosis; the selected miRNAs were confirmed with RT-PCR. miR-155 was up-regulated, but miR-698, -720, and -329 were down-regulated. Moreover, hepatic miR-155 was up-regulated at all-time points in the liver, but only at 7 h in spleen of mice with ALF. A significant correlation was observed between hepatic miR-155 and TNF/IL-6 in mice with ALF, which was supported by the findings in vitro showing up-regulated miR-155 in Raw264.7 cells and Hepa1-6 cells under LPS or D-GalN+TNF induction, respectively. Moreover, a correlation was observed between miR155 and TNF levels in vivo and in vitro. Conclusion: These data demonstrate that miR-155 regulates TNF-mediated hepatocyte apoptosis in ALF, which provides some useful information in both basic and clinical researches. Cite this article as: Zhang G, Yan C, Chen D, et al. Up-regulation of miR-155 contributes to TNF-mediated hepatocyte apoptosis in acute liver failure. Turk J Gastroenterol 2019; 30(5): 475-84.